Selection of Sheath Voltage Limiter for Mixed Overhead-Underground Cable in 220 kV Transmission Lines - Pham, Thanh Chung; Pham, Hong Thinh; Tran, Van Top (JST: Engineering And Technology For Sustainable Development, 2022)
This paper presents the most common methods of sheath bonding of transmission cables and the calculation of parameters, including rated voltage and energy absorption, of sheath voltage limiters for a mixed overhead-underground 220 kV transmission lines. The dependence of sheath voltage limiters parameters on the sheath types, system parameters such as the short-circuit capacity, the cable length, lightning current amplitudes, grounding resistance and cable installation are calculated in details. In this research, several methods in selecting sheath bonding types as well as sheath voltage limiters for a given set of conditions in mixed overhead-cable 220 kV transmission lines are proposed. The cross bonding permits to choose SVLs with the lowest rating voltage. However, the grounding resistance value of the tower at the junction between overhead lines and cables must be maintained at or below 3 Ω. The surrounding environment of cables changes, the required parameters of SVL to be selected must be recalculated to take the cable installation into account.